Perlindungan Hak Asasi Manusia Terhadap Anak Didik Pemasyarakatan Di Kalimantan Timur (Studi di Lembaga Pemasyarakatan dan Rumah Tahanan Negara) - Nur Arifudin (Jurnal Risalah Hukum, 2010)
The Indonesia children are expected favorable terms either in health, brightness, charm or kindness. Children must be protected from any violence, exploitations and discriminations. It is important to prepare them as the national next generation, in which children becomes main asset. Early development of children remains in the responsibility of family, community and nation. However, some factors influence this early development, such as biology, psychology, social, economic, and culture. Some children right may not be satisfied, therefore stimulating the mislead behavior pattern among children, which is next giving an impact on legal problem. The outlaw children should be specially attended recalling that their psychology development process is susceptible during this phase. The counseling infrastructure for the child convict in the convict institution and national prison has been in the low category in meeting the counseling demand of child convict.